2022
DOI: 10.3390/ijms23094764
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Alterations of the Endocannabinoid System in Psychiatric Disorders

Abstract: The therapeutic benefits of the current medications for patients with psychiatric disorders contrast with a great variety of adverse effects. The endocannabinoid system (ECS) components have gained high interest as potential new targets for treating psychiatry diseases because of their neuromodulator role, which is essential to understanding the regulation of many brain functions. This article reviewed the molecular alterations in ECS occurring in different psychiatric conditions. The methods used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 473 publications
1
11
0
2
Order By: Relevance
“…As such, a defined involvement for miR 200a and miR 200b in depression-like behaviour remains to be explored. However, several of the target genes, some of which by themselves act as regulators of gene expression (such as the transcription factors jun and atf3 ) have been demonstrated to be relevant to psychiatric disorders (including nr3c1 , the glucocorticoid receptor [ 70 , 71 ]; ntrk2, the receptor for brain-derived neurotrophic factor; [ 72 , 73 ] and cnr1 , the cannabinoid receptor 1 [ 74 , 75 ]). Hence, miR 200a and miR 200b and their target genes may constitute a gene regulatory network that forms the molecular basis for the pathophysiological events underlying the consequences early-life ID on affective behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…As such, a defined involvement for miR 200a and miR 200b in depression-like behaviour remains to be explored. However, several of the target genes, some of which by themselves act as regulators of gene expression (such as the transcription factors jun and atf3 ) have been demonstrated to be relevant to psychiatric disorders (including nr3c1 , the glucocorticoid receptor [ 70 , 71 ]; ntrk2, the receptor for brain-derived neurotrophic factor; [ 72 , 73 ] and cnr1 , the cannabinoid receptor 1 [ 74 , 75 ]). Hence, miR 200a and miR 200b and their target genes may constitute a gene regulatory network that forms the molecular basis for the pathophysiological events underlying the consequences early-life ID on affective behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is increasing regarding the role of eCB in mood regulation. Clinical studies have shown altered endocannabinoid signaling in psychiatric patients [ 182 ]. Genetic polymorphisms in CB1R and CB2R are associated with major depression, bipolar disorder, and resistance to therapy, which has been observed in depressed patients who have a single-nucleotide polymorphism in CB1R [ 183 , 184 , 185 , 186 ].…”
Section: Endocannabinoid System Emerging As a Pharmacotherapy Target ...mentioning
confidence: 99%
“…The endogenous cannabinoid or endocannabinoid system has been identified as playing a significant role in several psychiatric disorders, as well as in suicidal behaviour [142,143]. These effects appear to be mediated primarily through the cannabinoid type 1 (CB1) receptor, which is expressed at high levels in several key brain regions, including the prefrontal cortex and limbic system [144]. In a rat model, changes in social behaviour and sensitivity to physical or social pain caused by rejection were associated with an upregulation of CB1 receptors.…”
Section: E4 Cannabinoid Receptor Agonistsmentioning
confidence: 99%